Vibration control of multiferroic fibrous composite plates using active constrained layer damping. (June 2018) - Kattimani, S.C.; Ray, M.C.
Highlights: Vibration control of multiferroic fibrous composite plates is analyzed. Piezoelectric fibers are embedded into magnetostrictive matrix. Influence of coupled fields on vibration of the plate has been studied. Effect of fiber volume fraction, orientation and BCs on the vibration of plate is studied. Effect of fiber orientation angle in the 1–3 PZC layer of the ACLD has also been studied. Abstract: Geometrically nonlinear vibration control of fiber reinforced magneto-electro-elastic or multiferroic fibrous composite plates using active constrained layer damping treatment has been investigated. The piezoelectric (BaTiO3 ) fibers are embedded in the magnetostrictive (CoFe2 O4 ) matrix forming magneto-electro-elastic or multiferroic smart composite. A three-dimensional finite element model of such fiber reinforced magneto-electro-elastic plates integrated with the active constrained layer damping patches is developed. Influence of electro-elastic, magneto-elastic and electromagnetic coupled fields on the vibration has been studied. The Golla–Hughes–McTavish method in time domain is employed for modeling a constrained viscoelastic layer of the active constrained layer damping treatment. The von Kármán type nonlinear strain-displacement relations are incorporated for developing a three-dimensional finite element model. Effect of fiber volume fraction, fiber orientation and boundary conditions on the control of geometrically nonlinear vibration of the fiber reinforced magneto-electro-elastic plates is investigated. The performance of the active constrained layer damping treatment due to the variation of piezoelectric fiber orientation angle in the 1–3 Piezoelectric constraining layer of the active constrained layer damping treatment has also been emphasized.